Performance Evaluation and Impact of Grameen Bank on Social Development and Women Empowerment in Bangladesh - Chowdhury, Tanbir Ahmed; Somani, Sehel (International Journal of Social and Administrative Sciences, 2020)
Bangladesh is one of the fastest growing economies in Asia. However, it is still a developing country which is trapped in the vicious cycle of poverty. Nobel Laureater Professor Mohammad Yunus introduced the concept of Grameen Bank which focuses on providing small loans to poor people especially women in the rural areas of Bangladesh. Due to the huge success of Grameen Bank more micro finance institutions are replicating this model and hence more poor people are relying on this kind of projects. Therefore, it is important to know how sustainable Grameen Bank is and its true impact on social development and women empowerment. We have tried to assess the performance of Grameen Bank through different variables such as number of members, total deposits, loan to deposit ratio, capital adequacy ratio, scholarship schemes, beggars’ loan, house loan, micro enterprise loan, net income etc. For evaluating the performance of Grameen Bank 26 different trend equations and square of correlation coefficients have been tested with its different types of activities. The square of the correlation coefficient has also been calculated for all trend equations, out of which 21 shows r square is closer or more than 0.5 meaning well fitted trend lines. With the positive trend equations in most of the aspects this study proves that Grameen Bank has a better scope to grow in the future which will support the social and economic status of rural poor, particularly women.